THE FAIR VALUE AND ITS IMPACT ON THE DEFENSE INDUSTRY COMPLEX - A. A. Bakulina; P. P. Topchiy (Финансы: теория и практика, 2017)
Enterprises of the Defense Industry Complex are often faced with difficulties in making their reports in compliance with international standards for financial reporting and evaluation of assets and businesses at fair value, namely with IFRS Standard 13 “Fair Value Measurements”, for the lack of statutory regulation of reporting. The need to determine the fair value is because some of assets and liabilities essential for reporting are stated in the Russian Accounting Standards (RAS) at their historical value, which does not show the current (market) value of assets. As a result, foreign banks and investors are unable to judge the solvency of the lender. Determining the fair value allows the investor or the prospective lender to determine the current market value of available assets more accurately, which in turn gives the investors and lenders the real picture of the current state of an enterprise. The paper studies the main advantages of the harmonization of the national accounting and valuation for defense industry companies with international standards and defines the main levels of the impact of this harmonization. The Russian accounting system needs to absorb the most effective rules and traditions of foreign accounting practices, without losing the specifics of accounting at domestic defense enterprises.